Jonesy. Volume one - Humphries, Sam; Boyle, Caitlin Rose (BOOM! Box, 2016)
Jonesy is a regular teenager with the powers to make anybody fall in love with anyone else, but unfortunately, the powers don't work on herself. Left to her own non-magic devices, Jonesy learns that love sometimes isn't all it's cracked up to be.